STRATEGI PARTAI POLITIK DALAM MENGHADAPI PEMILU 2014 - Debora Sanur Lindawati (Jurnal Politica, 2013)
Political party is a means for political participation of the constitutional democracy to realize the national ideals of the Indonesian. Meanwhile, the election is an arena for people to express their freedom in choosing and selecting their leaders. In this context, political party as a political machine must be able to understand public aspiration, especially regarding legislatives and presidential candidates and their running mate the 2014 election. Otherwise, political parties will be more ignored by public. This condition will increase the member of people who will not exercise their political right in the coming election.